Cognitive profile of LRRK2‐related Parkinson's disease. Issue 5 (4th February 2015) - Srivatsal, Sindhu; Cholerton, Brenna; Leverenz, James B.; Wszolek, Zbigniew K.; Uitti, Ryan J.; Dickson, Dennis W.; Weintraub, Daniel; Trojanowski, John Q.; Van Deerlin, Vivianna M.; Quinn, Joseph F.; Chung, Kathryn A.; Peterson, Amie L.; et al.
Abstract Background Increasing evidence suggests that genetic factors play a role in the variability associated with cognitive performance in Parkinson's disease (PD). Mutations in the LRRK2 gene are the most common cause of monogenic PD; however, the cognitive profile of LRRK2‐related PD is not well‐characterized. Methods A cohort of 1, 447 PD patients enrolled in the PD Cognitive Genetics Consortium was screened for LRRK2 mutations and completed detailed cognitive testing. Associations between mutation carrier status and cognitive test scores were assessed using linear regression models. Results LRRK2 mutation carriers (n = 29) demonstrated better performance on the Mini Mental State Examination (P = 0.03) and the Letter‐Number Sequencing Test (P = 0.005). A smaller proportion of LRRK2 carriers were demented (P = 0.03). Conclusions Our cross‐sectional study demonstrates better performance on certain cognitive tests, as well as lower rates of dementia in LRRK2‐related PD. Future longitudinal studies are needed to determine whether LRRK2 mutation carriers exhibit slower cognitive decline. © 2015 International Parkinson and Movement Disorder Society